Postać Tejrezjasza w tradycji i literaturze antycznej - Sołtysik-Matłosz, Kamila (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
This article presents a profile of Tiresias, famous prophet of Thebes. The main question is a blindness and age of Tiresias connected with his authority.
Tiresias in the ancient tradition and literature
The fame of the ancient Boeotia was overshadowed by the fame of Athens and Sparta. But it was in Boeotia, where the fortune-telling had fully flourished and became an indispensable element of both private and public life in Greece. Here also Tiresias would prophecize, one of the most famous, Greek fortune-tellers, who dabbled in ornithomancy and telling the future from flames. D ue to the punishment sent by Hera, or according to other version, Athena, he had lost his eyesight. As a compensation for his suffering he was rewarded with the ability to foretell and exceptionally long life. The lack of eyesight did not cause harm to the ideal of kalokagathia, while other physical defects did. The Tiresias’s blindness was compensated with inner eyesight – seeing the future. Just like in reality the lack of eyesight sharpens other senses, in ancient literature we deal with the aforementioned interrelation between physical and inner eyesight. One may have healthy eyes but not see a thing, like Oedipus, or be blind but understand the essence of destiny, just like Tiresias. The eyes take on the proportions of a symbol and one may draw a conclusion that sensual perception gives in to the ability of the correct interpretation of events. Tiresias enjoyed great trust and was an authority among society, which would ask him for help when in need. Sometimes the role of fortune-teller was unrewarding and fortune-tellers were wrongly accused of trickery. The truth, which comes to light, clears Tiresias’s name, who now appears as a sage. The fact that the fortune-teller is perceived as a sage is connected not only with his divine mission but also with his age and experience. His old age is very often exposed and despite the fact that it is inconvenient, it holds Tiresias in high respect and he can account for some favors. Particular authors showed Tiresias in quite a different light and either human (Euripides) or divine element (Sophocles) may dominate in his figure.
Keywords: Tiresias; fortune-teller of Thebes